Regurgitant fraction as a load-dependent parameter in tricuspid regurgitation quantitation. (25th November 2020) - Liu, Y; Dong, L.L; Chen, B.Q; Zuo, W.X; Shu, X.H; Ge, J.B
Abstract: Background: Regurgitant fraction (RF) is an accepted tool for valvular lesion quantitation in the left heart, while its role in tricuspid regurgitation (TR) is less studied. Purpose: The aim of this study was to examine the determinants of RF in TR and its diagnostic utility for TR severity grading in comparison with regurgitant volume (RVol) using guideline recommended integrated algorithm as the reference standard. Methods: 114 pts with more-than-mild TR in the absence of pulmonary regurgitation or intracardiac shunt prospectively underwent 2D and 3D transthoracic echocardiography. 3D data sets of the right ventricle (RV) were obtained during breath hold. 3D RVol was calculated through subtracting the right ventricular outflow tract forward stroke volume (SV) from RV SV, where the outflow tract cross-sectional area was derived from single-view measured diameter. 3D RF was calculated by dividing 3D RVol with RV SV. 3D EROA was derived dividing 3D RVol with the velocity-time integral of TR. Results: 104 pts were included in the final analysis. 3D RF correlated well with 3D RVol (r=0.80, P<0.0001). Factors encompassing aetiology (organic/functional), heart rate, systolic pulmonary arterial pressure (sPAP), cardiac output, 3D EROA and RV end-diastolic volume index were included in multiple linear regression (R2=0.85), which demonstrated that RF was associated with sPAP (P<0.0001) but not RV end-diastolic volume index (P=0.116). Receiver operator characteristic analysis revealed significant difference in area under the curve between 3D RVol and 3D RF (Z=2.873, P=0.004). Such difference diminished in pts with elevated sPAP (Z=1.226, P=0.220), while remained in those with normal range sPAP (Z=2.897, P=0.004). Conclusions: 3D RF is less dependent on volume load but is significantly influenced by pressure load in TR quantitation. The diagnostic power of 3D RF in differentiating severe TR is comparable with 3D RVol in pts with elevated sPAP but is limited in pts with normal range sPAP. Funding Acknowledgement: Type of funding source: None